A bitter herbal medicine Gentiana scabra root extract stimulates glucagon-like peptide-1 secretion and regulates blood glucose in db/db mouse. (22nd August 2015) - Suh, Hyo-Weon; Lee, Ki-Beom; Kim, Ki-Suk; Yang, Hea Jung; Choi, Eun-Kyeong; Shin, Min Hee; Park, Yong Seek; Na, Yun-Cheol; Ahn, Kwang Seok; Jang, Young Pyo; Um, Jae Young; Jang, Hyeung-Jin
Abstract: Ethnopharmacological relevance: Gentiana scabra root extract (GS) is frequently prescribed as an internal remedy in traditional Korean medicine for treatment of diabetes mellitus. GS contains bitter iridoid glycosides including loganic acid, gentiopicrin, trifloroside, and rindoside. We previously reported that the intestinal bitter taste sensation stimulates GLP-1 secretion, and thereupon hypothesized that the blood glucose regulatory effect of GS is due to its GLP-1 secreting effect in enteroendocrine L cells. Materials and method: We studied GLP-1 secreting effect of GS treatment and its cellular downstream mechanism in human enteroendocrine NCI-H716 cells using the G protein-coupled receptor (GPCR) pathway inhibitors. Intracellular calcium assay also demonstrated the signal transduction pathway stimulated by the GS treatment. Using db/db mice, we performed oral glucose tolerance test (OGTT) to examine the blood glucose lowering effect of GS administration. We also collected the mouse plasma during the OGTT to measure the GLP-1 and insulin levels. Result: We demonstrated dose-dependent GLP-1 secreting effect of GS on the NCI-H716 cells. The GLP-1 secreting effect of GS is mediated by the G protein βγ-subunit and inositol triphosphate. Using db/db mice, we found that the effect of GS on lowering blood glucose is due to its GLP-1 secretion, and consequential insulinotropic effect. The chemical fingerprint of GS was obtained through a direct analysis in realtime mass spectrometry (DART-MS) and high-performance liquid chromatography (HPLC)/MS. Through the GLP-1 secretion study, we found that loganic acid, an iridoid glycoside, contributes to the GLP-1 secreting effect of GS. Conclusion: The findings of this study highlight the potential of exploiting the antidiabetic effect of GS on type 2 diabetes mellitus patients. Graphical abstract: